Political-economic correlates of environmental policy - Andreas Kammerlander; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2020)
Does globalization lead to environmental degradation? What is the role of democracy for environmental performance and do left-wing governments really care more about the environment? Using a comprehensive measure of environmental performance, we test these three hypotheses for a panel of 134 countries for the period 2007-2016. Our findings show that globalization leads to better environmental performances. Interestingly, this result is predominantly driven by social, not by economic or political globalization. Although we find evidence that left-wing governments perform better than right-wing governments, it is centrist governments that have the highest environmental performance. The political system, i.e. democracy, turns out insignificant in all specifications.
Keywords: F64; O13; Q5; Q56; 330; Environment; Globalization; Political Orientation; Democracy; Environmental performance index; KOF globalization index